Pengaruh Pemberian Virgin Coconut Oil Terhadap Kejadian Infeksi Saluran Pernapasan Akut Pada Balita Gizi Kurang - Nur Asmi; A. Fatwa Tenriawaru (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction; malnutrition can make a person more susceptible to infection, and infection also contributes to malnutrition, leading to a vicious cycle. Aim; assessing the effect of giving Virgin Coconut Oil (VCO) on weight gain and the incidence of ARI in malnourished children under five. Method; This type of research is a quasi-experimental study with a randomized pretest-posttest control group design. This study used VCO and PMT in the treatment group and PMT alone in the control group. Result; There was no difference in changes in body weight gain between the treatment group and the control group with a value of P = 0.937, there was a difference in changes in the form of a decrease in the frequency and duration of ARI illness between the treatment group and the control group where the P-value was P = 0.018 and P = 0.010, respectively. Conclusion from the study is that VCO cannot help increase the weight of under-nutrition children, but it can help reduce the frequency and duration of ARI illness